Visceral leishmaniasis in Brazil: trends and challenges Leishmaniose visceral no Brasil: evolução e desafios - Ana Nilce Silveira Maia-Elkhoury; Waneska A. Alves; Márcia Leite de Sousa-Gomes; Joana Martins de Sena; Expedito A. Luna (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
The urbanization of visceral leishmaniasis in Brazil has been related to environmental changes, migration, interaction and spread of sylvatic reservoirs and infected dogs to areas with no transmission, and adaptation of the vector Lutzomyia longipalpis to the peridomiciliary environment. From 1980 to 2005, Brazil recorded 59,129 cases of visceral leishmaniasis, 82.5% of which in the Northeast region. Visceral leishmaniasis gradually spread to other regions of the country: in 1998 these other regions reported 15% of all cases, but by 2005 this proportion had increased to 44%. From 1998 to 2005, indigenous cases were reported in 1,904 different municipalities of the country (34.2%). Reservoir and vector control pose major challenges for disease control, since there is a need for better knowledge of vector behavior in urban areas, and control activities involve high operational costs. In recent years the Brazilian Ministry of Health has supported research on the laboratory diagnosis of infection and disease in humans and dogs, treatment of patients, evaluation of the effectiveness of control strategies, and development of new technologies that could contribute to the surveillance and control of visceral leishmaniasis in the country. A urbanização da leishmaniose visceral tem sido relacionada a modificações ambientais causadas por ações antrópicas, pelo rápido processo migratório, pela interação e mobilização de reservatórios silvestres e cães infectados para áreas sem transmissão, e pela adaptação do vetor Lutzomiya longipalpis ao peridomicílio. Entre 1980 e 2005, o Brasil registrou 59.129 casos de leishmaniose visceral, sendo 82,5% na Região Nordeste. Gradativamente, a leishmaniose visceral expandiu-se para as regiões Centro-Oeste, Norte e Sudeste, passando de 15% dos casos em 1998 para 44% em 2005. Entre 1998 e 2005 foram registrados casos autóctones em 1.904 (34,2%) diferentes municípios brasileiros. O controle vetorial e de reservatórios representam os maiores desafios para o controle da doença, dado a necessidade de melhor conhecer o comportamento do vetor no ambiente urbano, as dificuldades operacionais e o alto custo de execução. Nos últimos anos, o Ministério da Saúde tem investido em pesquisas sobre diagnóstico laboratorial humano e canino, tratamento dos pacientes, avaliação da efetividade das estratégias de controle, bem como de novas tecnologias que possam contribuir na implementação das ações de vigilância e controle da leishmaniose visceral no Brasil.